Impact of Nonlinear Radiation and Irregular Heat Sources on 3D Rotating Flow of Nanofluids with SWCNTs and MWCNTs - Kumar, P. B. Sampath; Veeranna, Y.; Manohar, S. H.; Gireesha, B. J.; Sunitha, M. S. (Journal of Applied Nonlinear Dynamics, 2026)
This study presents a comparative analysis of the engineering applications of single-walled and multi-walled carbon nanotubes (SWCNTs and MWCNTs). The investigation focuses on the three-dimensional rotating flow of a nanofluid with nonlinear convection over an elongated surface. The heat transfer characteristics are examined under the influence of nonlinear radiation, an irregular heat source, and convective boundary conditions. Water serves as the base fluid, embedded with both SWCNTs and MWCNTs. Solutions are derived using the shooting technique, and the results are comprehensively displayed through tables and graphical representations. Detailed discussions of various flow field characteristics are provided. The findings indicate that MWCNTs exhibit a higher heat transfer coefficient compared to SWCNTs. Additionally, the presence of irregular heat sources enhances the temperature of the nanofluid.